Resilience science must-knows: Nine things every decision-maker should know about resilience - Norström, Albert; Queiroz, Cibele; Nyström, Magnus; Jiménez-Aceituno, Amanda; Jonsson, Amanda; McFadden, Alexandra; Milton, Nirvana; Peterson, Garry; Barnes, Michelle; Béné, Christophe; Biggs, Reinette; Boyd, Emily; et al. (Stockholm Resilience Centre, 2025)
Resilience has become a central consideration across practice, policy, and business. It is increasingly integrated into public health strategies, private-sector risk management, corporate planning, development, and financial investment. This growing interest in resilience is not by chance. In recent years, the world has faced a variety of overlapping crises, from climate extremes and military conflicts to the COVID-19 pandemic and cascading disruptions in trade and food systems. Volatility is no longer an exception; it is the new norm. Decision-makers across regions and sectors urgently need clear, science-based, and actionable knowledge to maintain the resilience of people and the planet and to ensure societies have the capacity to cope, adapt, and transform in order to thrive amid uncertainty. Yet, despite a wealth of research into the science of resilience, the findings often remain complex, making them difficult to translate into actionable insights for leaders outside the scientific community. The Resilience Science Must-Knows address this challenge head-on by distilling decades of cutting-edge resilience science into nine critical Must-Knows refined through dialogue with decision-makers.